Early Pleistocene depositional and environmental conditions at Dachangliang, Nihewan Basin, NE China - H. Moghazi, Ahmed; Zhao, Hailong; Zhang, Chengjun; Eythorsdottir, Elísabet A.; Mischke, Steffen (Frontiers in Earth Science, 2024)
The Pleistocene sediments of Nihewan Basin in NE China are intensively studied since ca. 100 years because of its rich mammalian fossil record and abundant stone-artifact-bearing layers. To better understand the mechanisms underlying past climate and environmental changes in the basin, three sediment sections at the Dachangliang location were investigated using a multi-proxy toolbox of sedimentological, magnetic susceptibility (MS) and micropalaeontological analyses. The exposed sediments are lithologically mostly relatively homogeneous, with grain sizes in a relatively small range. However, variations in colour, bedding structures, concentrations of magnetic minerals and the ostracod assemblage were used to correlate the three sections to form the synthetic NH-T section of 86.2-m total length. The sediments mainly represent varicoloured silt of probably reworked loess deposits, partially interbedded with fine sand layers and minor contributions of clay particles. These sediments are interpreted to have accumulated in wetlands alternating with deposition on an alluvial plain, and with a lacustrine setting which probably existed from time to time. These different depositional settings are expressed in the three dominant fine to coarse silt-sized components and the ostracod-assemblage changes (mostly Limnocythere flexa, Ilyocypris spp. and Leucocythere sp.). The recorded ostracods of laterally apparently consistent white marl beds (dominantly Cytherissa lacustris) were used to stratigraphically correlate these sections. The resulting NH-T section was further correlated with the three proximal artefact-bearing sections Majuangou, Banshan and Xiantai which have published magnetostratigraphic data. The correlation shows that the investigated sedimentary sequence was probably formed between ca. 1.7 and 0.9 Ma. The relatively continuous synthetic sequence NH-T represents three main wetter periods with three intervening drier intervals, possibly synchronous with interglacial (S23-S20, S15-S13 and S10-S9) and glacial (L20-L18, L17-L16 and L13-L11) periods which were previously inferred from the palaeoclimatic records of the Chinese Loess Plateau (CLP) in the SW of the Nihewan Basin.